Development of a three-dimensional icing simulation code in the NSMB flow solver. (2016) - Pena, Dorian; Hoarau, Yannick; Laurendeau, Éric
An icing model is developed in the Navier-Stokes multi-block (NSMB) compressible solver. The code implemented in this study is based on an Eulerian formulation for droplets tracking solved implicitly by means of CGSTAB or SIP methods, a modified iterative Messinger model using an improved water runback scheme for ice thickness calculation and three-dimensional mesh deformation to track the ice/air interface through time. The whole process is parallelised with MPI for efficient calculations. Validation is performed on several test cases including NACA23012 and NACA00012 airfoils and ONERA-M6 swept wing. Pressure coefficients around iced 23012 airfoil are compared with experimental data. Rime icing is computed on a DLR-F6 wing/body configuration. In all studied cases, the results are in good agreement with the literature.